The Association Between Social Interaction and Nutritional Status: A Cross-Sectional Study in a Health-Promoting Campus Setting - Hafid, Fahmi; Taufiqurrahman, Taufiqurrahman; Sumasto, Hery; Nuswantari, Atika; Arifah, Jazilah Nur; Sariman, Sarina; Isaura, Emyr Reisha (Journal of Health and Nutrition Research, 2025)
This study aimed to analyze the relationship between fruit and vegetable intake, physical activity, nutritional status, and social interaction among the academic community at Polkesbaya Corner, a health-promotion facility developed by Poltekkes Kemenkes Surabaya as part of the “Healthy Campus Initiative.” Polkesbaya Corner serves as a campus-based innovation designed to integrate nutrition education, physical activity, and social engagement, supporting the 3rd Sustainable Development Goal (Good Health and Well-being). A cross-sectional study was conducted among 363 respondents selected through proportionate stratified random sampling. Data were collected using a Food Frequency Questionnaire (FFQ), 24-hour dietary recall, the International Physical Activity Questionnaire (IPAQ), anthropometric measurements, and sociometric observation. A statistical association was observed between social interaction and nutritional status (p = 0.024), whereas fruit and vegetable intake and physical activity were not significantly associated with this outcome. Overall, 52.3% of respondents had normal nutritional status, while 31.7% were overweight. Most participants performed light physical activity (79.3%) and consumed sautéed vegetables (74.1%) and sliced fruits (68.9%). These findings highlight the crucial role of social engagement in promoting healthy behaviors within the campus environment. Therefore, Polkesbaya Corner can serve as a “living laboratory” to foster a culture of health by integrating nutrition education, physical activity, and social participation—supporting the national health promotion agenda and the achievement of SDG 3.